PENGARUH PENDAPATAN KEPALA KELUARGA TERHADAP PENDIDIKAN FORMAL ANAK - Mukhammad Imam Muhdi (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This study aims to know the effect of income There are heads of households to the formal education of children. This research is quantitative research. Its population is around the head of a family residing in RT.07 RW.02 some 54 heads of families. The overall sample population using sampling techniques saturated. Collecting data using questionnaires. The data analysis technique used is the univariate and bivariate analyzes. Bivariatnya analysis using Chi-kuadrat.Data result showed 53.7% of respondents income 500,000, - <p <1.000.000, -, the remaining 29.6% income <500.000, - and 16.7% income> 1,000,000 , -. Formal education the majority of elementary school children by 38% and 27.8% junior, 26.6% and 7.6% junior college graduates. Results of analysis by Chi-square test results obtained X2 = 10.46394. X2hitung <X2tabel ie 10.46394 <12.592 so Ho accepted and Ha rejected. It means that there is no effect between income family heads to formal education of children. The degree of influence of the head of the family income on children's education is 0.12. While the Q value is between 0.10 and 0.29 then the corresponding provisions Dervish can be seen that the degree of influence of the head of the family income on children less closely formal education.